Quantifying the Impact of Red Tape on Investment: A Survey Data Approach - Bruno Pellegrino; Geoffery Zheng (Center for Economic Studies and ifo Institute (CESifo), 2023)
An important strand of research in macro-finance investigates which factors impede enterprise investment, and quantifies their aggregate cost. In this paper, we make two contributions to this literature. The first contribution is methodological: we introduce a novel framework to calibrate macroeconomic models with firm-level distortions using enterprise survey micro-data. The core of our innovation is to explicitly model the firms' decisions to report the distortions they face in the survey. Our second contribution is to apply our method across seven countries to characterize the distribution of these distortions and estimate the GDP loss induced by distortionary red tape. Our estimates are based on a dynamic general equilibrium model with heterogeneous firms whose capital investment decisions are distorted by red tape. We find that the aggregate cost of red tape varies widely across the countries in our dataset, with an average cost of of 0.8% of annual GDP. Our framework opens up a new range of applications for enterprise surveys in macro-financial modeling and policy analysis.
Keywords: C83; E20; E60; G38; H10; H20; K20; O10; O40; 330; bureaucracy; growth; investment; legislation; misallocation; red tape; regulations; survey